AB1170 Cost Minimization Study After Dose Optimization of Anti-TNF Alpha in a Specialized Outpatient Clinic on Biological Therapy (BT). (9th June 2015) - Manrique-Arija, S.; Ureña, I.; Ordoñez, M.C.; Coret, V.; Cano, L.; Jimenez-Nuñez, F.G.; Mena-Vazquez, N.; Romero-Barco, C.M.; Irigoyen, M.V.; Belmonte, Ά.; Rodriguez, M.; Ponce, A.; et al.
Abstract : Objectives: To estimate the cost reduction in the use of anti- TNFα therapies in patients with different rheumatic diseases when dose modifications are undertaken in clinical practice in a specialized outpatient clinic of a tertiary hospital during 2013-2014 and to describe clinical and analytical characteristics of these patients. Methods: Design: Cost-minimization observational, retrospective study under conditions of clinical practice. Patients: All patients who received a dose of anti-TNFα different from the recommended in technical specifications and were followed up in a specialized BT outpatient clinic in a Spanish Rheumatology department during 2013 and 2014 were included. Protocol: Reductions in treatment dose or frequency dose were established empirically and were carried out by their rheumatologist in those patients who were in remission (DAS 28<2, 6) for at least 6 consecutive months without steroids. Variables: Outcome 1°: Reduction of biannual average cost in euros (absolute and per treatment) of anti-TNFα treatments in patients who are in dose reduction compared to full-dose according to authorization specifications during 2013 and 2014. Secondary variables: demographics, type of rheumatic disease, clinical and laboratory data were collected. The cost reduction was calculated by comparing actual expenditures (after modifying treatment dose in clinical practice) with the theoretical costs (official price). Statistical analysis: a descriptive analysis of the sample of patients was performed. Reducing biannual absolute costs and by treatment after the adequacy of dose in clinical practice were calculated. Results: During 2013-2014, the dose of anti-TNFα of 76 patient were modified in clinical practice after reaching clinical remission: DAS28 [mean (SD)]: 2.34 (0.62) or BASDAI [mean (SD)]: 2.72 (1.09) and no radiographic progression. During this period, 5 patients discontinued anti-TNFα (2 adverse effects; 2 patients' decision, and 1 remission). The epidemiological and clinical-laboratory characteristics are described in the table by diseases. 34 out of 76 pts were treated with Etanercept, 20 with Adalimumab and 22 with Infliximab. No patient with Golimumab, Abatacept, Anakinra or Certolizumab reduced the dose during 2013-2014. Dose modifications of TB conducted in clinical practice for 2013- 2014 represented an absolut saving of 602, 572.49€ (Table ). In 2013 the absolute reduction in costs was 275, 443.95€ (Etanercept: 158, 030.47€; Adalimumab: 62, 917.21€ and Infliximab: 54, 496.27 €) in a total of 61 patients and in 2014 of 327, 128.54€ (etanercept: 178, 289.00€; Adalimumab: 87, 055.35€ and Infliximab: 61, 784.19 €) in a total of 71 patients achieving a greater efficiency of the treatments. Conclusions: In rheumatic diseases we may adjust the anti-TNFα doses in patients who go into remission and therefore reduce associated costs being more efficient. We believe it is important to create outpatient clinics specialized in BT where a tight control and an individualized treatment are carried out. Etanercept was the most used among patients with anti-TNFα modified dose. Disclosure of Interest: None declared